Enhancing Competency of ICU and NICU Nurses in Patient Safety Implementation for Infection Prevention in Invasive Procedures at Ratu Mas Hospital, 2025 - Sontina Saragih; Yudica Rosalina Nainggolan (Jurnal Masyarakat Madani Indonesia, 2026)
Patient safety is a fundamental principle of modern healthcare, particularly in intensive care settings where critically ill patients are at heightened risk of healthcare-associated infections (HAIs) arising from frequent invasive procedures. Healthcare workers in intensive care units (ICUs) and neonatal intensive care units (NICUs) require periodic competency enhancement to ensure consistent, evidence-based implementation of patient safety principles. This community service activity aimed to improve the knowledge and competency of ICU and NICU healthcare workers at Ratu Mas Hospital, Binjai, in implementing patient safety principles, with particular emphasis on infection prevention during invasive procedures. A multimodal educational approach was employed, comprising didactic lectures, interactive discussions, procedure demonstrations, and knowledge evaluation using standardized pre-test and post-test instruments consisting of 15 multiple-choice questions covering hand hygiene, aseptic technique, and infection prevention in invasive procedures. The training was conducted on October 28–29, 2025, with 45 participants including ICU nurses, NICU nurses, and other clinical staff. Evaluation results demonstrated significant improvements in mean knowledge scores across all assessed domains: hand hygiene increased from 58.4 to 85.6 (+27.2 points); aseptic technique from 56.8 to 83.7 (+26.9 points); and infection prevention in invasive procedures from 61.2 to 87.4 (+26.2 points), yielding an overall mean improvement from 58.8 to 85.6 (+26.8 points). The training proved effective in enhancing healthcare workers’ knowledge and should be delivered on a regular basis as an integral component of quality improvement and patient safety culture development in ICU and NICU settings. To translate these knowledge gains into sustained clinical practice, the institution is recommended to implement periodic hand hygiene audits, regular supervision, observational assessment of aseptic technique, and continuous quality improvement initiatives to sustain the patient safety culture.